Оценка эффективности рекламы в интернете - Андреев, Д.А.; Апатова, Н.В. (Культура народов Причерноморья, 2014)
В статье проведен анализ современного состояния интернет–рекламы в Украине и
выявлены основные проблемы в её развитии. Рассмотрены основные особенности и факторы, влияющие
на рекламу в Интернете. Исследованы основные виды интернет–рекламы с описанием их особенностей
и возможностей. Исследованы основные подходы и показатели, необходимые для оценки
эффективности интернет–рекламы. В статье подробно рассмотрен комплексный подход для оценки
эффективности рекламы в Интернете. У статті проведено аналіз сучасного стану інтернет–реклами в Україні та виявлено основні
проблеми в її розвитку. Розглянуто основні особливості та фактори, які впливають на рекламу в
Інтернеті. Досліджено основні види інтернет–реклами з описом їх особливостей і можливостей.
Досліджено основні підходи та показники, необхідні для оцінки ефективності інтернет–реклами. У
статті докладно розглянуто комплексний підхід для оцінки ефективності реклами в Інтернеті. The rapid growth of the Internet around the world made the Internet an effective business
environment. Internet now allows you to advertise, make payments, buy and sell products, share and find
information, travel, etc. Internet advertising market in Ukraine every year is growing rapidly. Advertise their
products and services on the Internet every year becomes more and more popular, as most people already have
access to the global network. On the Internet advertising market is observed gradual monopolization by pooling
large companies. For effective management of Internet advertising should know all its types and features, and
the ability to assess its effectiveness in the Internet environment.
Using comprehensive approach to assess the effectiveness of Internet advertising can more fully reflect the
degree of economic and communicative impact on consumers, to identify the strengths and weaknesses of ad
campaigns, improve business efficiency through integrated analysis of ad campaigns. The Internet advertising market in Ukraine has several significant problems. First, primary problem lies in lack
of money an advertiser when a large amount of traffic, and television advertising in Ukraine ahead of online
advertising, covering a greater number of consumers. Secondly, the problem remains the selling of own traffic
through ad networks, rather than selling it directly. A site that has no definite narrow subjects, it is difficult to
attract the attention of advertisers, because most visitors will not be interested in advertising. The third problem
is the Russian dumping, which manifests itself in the fact that those who cannot sell in Russia Ukrainian traffic
at specific prices, offer it at reduced prices in Ukraine and thus dumping market.